2018
DOI: 10.1159/000491528
|View full text |Cite
|
Sign up to set email alerts
|

Apigenin Retards Atherogenesis by Promoting ABCA1-Mediated Cholesterol Efflux and Suppressing Inflammation

Abstract: Background/Aims: The development of atherosclerosis is accompanied by escalating inflammation and lipid accumulation within blood vessel walls. ABCA1 plays a crucial role in mediating cholesterol efflux from macrophages, which protects against atherogenesis. This research was designed to explore the effects and underlying mechanisms of apigenin (4’, 5, 7-trihydroxyflavone) on ABCA1-mediated cellular cholesterol efflux and LPS-stimulated inflammation in RAW264.7 macrophages and apoE-/- mice. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(40 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…Sr-B1 plays an antiatherogenic role, and is responsible for selective uptake of cholesterol esters from high-density lipoprotein (Hdl) and LDL, and free cholesterol efflux to lipoprotein acceptors (41). aBca1, a major protective factor against aS, is involved in directing cholesterol efflux from macrophages (42). ABCA1 can transfer excess free cholesterol to cholesterol acceptors such as ApoA-I or ApoE, thus promoting cholesterol efflux and inhibiting macrophage foam cell formation (42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sr-B1 plays an antiatherogenic role, and is responsible for selective uptake of cholesterol esters from high-density lipoprotein (Hdl) and LDL, and free cholesterol efflux to lipoprotein acceptors (41). aBca1, a major protective factor against aS, is involved in directing cholesterol efflux from macrophages (42). ABCA1 can transfer excess free cholesterol to cholesterol acceptors such as ApoA-I or ApoE, thus promoting cholesterol efflux and inhibiting macrophage foam cell formation (42).…”
Section: Discussionmentioning
confidence: 99%
“…aBca1, a major protective factor against aS, is involved in directing cholesterol efflux from macrophages (42). ABCA1 can transfer excess free cholesterol to cholesterol acceptors such as ApoA-I or ApoE, thus promoting cholesterol efflux and inhibiting macrophage foam cell formation (42). The reduced Sr-B1, aBca1 and apoe expression levels, and elevated Sr-a expression were suggestive of cholesterol homeostasis disturbance at the molecular level in the MalaT1-silenced macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Apigenin in LPS-exposed macrophages reduces TLR-4, MyD88 and phosphorylation of IκKB levels through nuclear NF-κB p65 signaling pathway [192]. Ren et al confirmed these results in vivo, demonstrating that in LPS-challenged apoE deficient mice, treatment with apigenin determined the reduction of TLR-4 and NF-κB p65 levels and lessened the macrophages and SMC number in atherosclerotic regions [192]. Apigenin inhibited the expression of VCAM-1 and IκKB kinase and prevented the adhesion of U937 monocytes to EC exposed to high-glucose (30 mM) concentrations [193].…”
Section: Flavanonesmentioning
confidence: 98%
“…Regarding the effect of apigenin on cytokine secretion, it has been shown that apigenin reduced IL-6 and TNF-α secretion in LPS-stimulated RAW 264.7 macrophages [190] and decreased TNF-α release in the media of LPS-activated macrophages [191]. Apigenin in LPS-exposed macrophages reduces TLR-4, MyD88 and phosphorylation of IκKB levels through nuclear NF-κB p65 signaling pathway [192]. Ren et al confirmed these results in vivo, demonstrating that in LPS-challenged apoE deficient mice, treatment with apigenin determined the reduction of TLR-4 and NF-κB p65 levels and lessened the macrophages and SMC number in atherosclerotic regions [192].…”
Section: Flavanonesmentioning
confidence: 99%
“…Here, we summarize the key findings of the biological and pharmacological actions of apigenin (Table 1 (Tab. 1) ; References in Table 1: Ahmad et al, 2019[ 1 ]; Ai et al, 2017[ 2 ]; Amiri et al, 2018[ 3 ]; Britto et al, 2017[ 4 ]; Charalabopoulos et al, 2019[ 5 ]; Chen et al, 2017[ 7 ], 2019[ 8 ], 2020[ 6 ]; Choi et al, 2018[ 9 ]; Dean et al, 2018[ 10 ]; Feng et al, 2017[ 11 ]; Ganai, 2017[ 13 ]; Han et al, 2017[ 15 ]; Hassan et al, 2017[ 16 ]; He et al, 2020[ 17 ]; Huang et al, 2020[ 19 ]; Jiang et al, 2018[ 20 ]; Jiao et al, 2019[ 21 ]; Jing et al, 2019[ 22 ]; Kang et al, 2018[ 23 ]; Ketkaew et al, 2017[ 24 ]; Lee et al, 2019[ 26 ]; Li et al, 2017[ 28 ], 2019[ 29 ], 2020[ 27 ]; Liu et al, 2018[ 30 ]; Lu et al, 2019[ 31 ]; Malik et al, 2017[ 32 ]; Mirzoeva et al, 2018[ 33 ]; Mrazek et al, 2019[ 34 ]; Nelson et al, 2017[ 36 ]; Pang et al, 2019[ 37 ]; Qiu et al, 2019[ 38 ]; Quan et al, 2020[ 39 ]; Rašković et al, 2017[ 40 ]; Ren et al, 2018[ 41 ]; Safari et al, 2018[ 42 ]; Sánchez-Marzo et al, 2019[ 44 ]; Sang et al, 2017[ 45 ]; Sharma et al, 2018[ 48 ]; Siddique and Jyoti, 2017[ 49 ]; Stump et al, 2017[ 50 ]; Thangaiyan et al, 2018[ 52 ]; Tong et al, 2019[ 53 ]; Wang et al, 2017[ 54 ], 2018[ 56 ], 2019[ 55 ]; Wu et al, 2017[ 57 ]; Xu et al, 2018[ 58 ]; Zare et al, 2019[ 59 ]; Zhang et al, 2017[ 61 ], 2018[ 63 ], 2019[ 62 ], 2020[ 60 ]; Zhao et al, 2019[ 64 ]; Zhong et al, 2017[…”
mentioning
confidence: 99%